A Pilot Study of Clarifying (Fining) Agents and Their Effects on Beer Physicochemical Parameters - Sterczyńska, Monika; Zdaniewicz, Marek; Stachnik, Marta (MDPI AG, 2026)
The role of science and technology in enhancing beer quality is crucial amid growing market demands. This pilot study assessed the clarity and physicochemical stability of laboratory beers treated post fermentation with three clarifying (fining) agents: two chitosan-based and one collagen-based (fish bladder/isinglass). The beers were brewed with Polish barley malt and hops (alpha acids 7.5% and 14.5%). The measured parameters included pH, colour, turbidity, viscosity, surface tension, and foam volume. Within this small-scale, low-power dataset, both the collagen- and chitosan-based agents improved clarity, with the collagen agent showing the lowest turbidity in this sample. The clarifying agents also influenced the colour and surface tension, while the pH was largely unchanged. The foam volume increased with fining. Shelf-life checks suggested improved stability in clarified beers, with no clear differences between agents under these conditions. These findings are preliminary. The results should be interpreted cautiously due to the limited number of replicates. Larger scale studies with adequate replication are required before translating these observations into brewing practice. Chitosan’s effectiveness as a clarifying agent aligns with its high charge density and ability to coagulate suspended particles. This study underscores the importance of selecting appropriate clarifying agents to optimize beer clarity and stability while maintaining essential physicochemical properties. These findings contribute to the brewing industry’s efforts to meet consumer expectations for high-quality, stable beer products.